Electron spectrum in conﬁned cylindrical nanoheterosystem with ﬁnite depth of potential well - Holovatsky, V.A.; Voitsekhivska, O.M.; Mikhalyova, M.J.; Tkach, M.M. (Condensed Matter Physics, 2000)
Electron spectrum in cylindrical quantum dot HgS embedded into ZnS medium is calculated using the variational method with variational parameter in Hamiltonian. The dependence of energy spectrum on the quantum well sizes is established. The electron spectrum calculated in the framework of inﬁnitely deep potential well is compared to the one obtained within the variational method. It is shown that the ﬁrst method gives satisfactory results for the ground level only and at rather big sizes of quantum well.